Cost‐Effectiveness of Maintenance Hemodialysis in Japan. Issue 5 (21st September 2015) - Takura, Tomoyuki; Nakanishi, Takeshi; Kawanishi, Hideki; Nitta, Kosaku; Akizawa, Tadao; Hiramatsu, Makoto; Kawasaki, Tadayuki; Kukita, Kazutaka; Soejima, Hidehisa; Hirakata, Hideki; Yoshida, Toyohiko; Miyamoto, Takashi; et al.
Abstract The cost‐effectiveness according to primary disease or dialysis duration has never been analyzed with respect to maintenance hemodialysis (MHD). Study candidates were > 20 years of age and had received hemodialysis for at least 6 months. Hemodialysis patients were prospectively observed for 36 months, and patient utility was assessed based on the Euro‐QOL 5‐dimensions (EQ‐5D), from which the quality adjusted life years (QALYs) were estimated. Medical costs were calculated based on medical service fees. The cost‐effectiveness defined as the incremental cost utility ratio (ICUR) was analyzed from a social perspective. A total of 29 patients (mean age; 59.9 ± 13.1 years) undergoing 437 dialysis sessions were analyzed. Utility based upon the EQ‐5D score was 0.75 ± 0.21, and the estimated total medical cost for one year of MHD treatment was 4.52 ± 0.88 US10 000. ICUR was 6.88 ± 4.47 US10 000/QALY on average, and when comparing ICUR based on the causes of kidney failure, the value for diabetic nephropathy was found to be higher than that for glomerulonephritis (8.17 ± 6.28 vs. 6.82 ± 4.07). ICUR after 36 months observation increased mainly in the patients below 65 years of age (All; P < 0.05, <65; P < 0.01, 65≤; not significant). MHD is a treatment that could improve the socioeconomic state of elderly patients with end‐stage kidney disease (ESKD), but the ICUR for diabetic nephropathy was higher than that for glomerulonephritis.